2021
DOI: 10.3390/ijms22147742
|View full text |Cite
|
Sign up to set email alerts
|

Combined Exposure to Diazinon and Nicotine Exerts a Synergistic Adverse Effect In Vitro and Disrupts Brain Development and Behaviors In Vivo

Abstract: A real-life environment during pregnancy involves multiple and simultaneous exposures to toxic chemicals. Perinatal exposures to toxic chemicals have been reported to exert an inhibitory effect on mouse neural development and behaviors. However, the effect of combined exposures of organophosphate and nicotine has not been previously reported. In this study, we investigated whether a combined exposure of diazinon and nicotine can have a synergistic effect. The effects of the combined chemical exposure on cell v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…If mice turned on the beam or felt down, they were replaced immediately. 52,53 Trained mice were randomly selected to form five groups (six animals per group). Instead of POX-and PTE-loaded nanoreactors, equal volumes of saline solutions were s.c. and i.v.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…If mice turned on the beam or felt down, they were replaced immediately. 52,53 Trained mice were randomly selected to form five groups (six animals per group). Instead of POX-and PTE-loaded nanoreactors, equal volumes of saline solutions were s.c. and i.v.…”
Section: Methodsmentioning
confidence: 99%
“…Mice were given three trials with at least 15 min of recovery time between each trial. If mice turned on the beam or felt down, they were replaced immediately. , Trained mice were randomly selected to form five groups (six animals per group).…”
Section: Methodsmentioning
confidence: 99%
“…There are some excellent examples of the adverse effects of EDCs in the authors' laboratory. Bonn Lee and colleagues reported the synergistic effects of the developmental neurotoxicity of the combined exposure to the EDCs nicotine, diazinon, and organophosphate [15]. Tran Nam et al reported that maternal exposure of octamethylcyclotetrasiloxane caused abnormal neurodevelopment and behaviors [16].…”
Section: Edcs and Related Diseasementioning
confidence: 99%
“…Yet, accumulation of these OPs have been apparent in crop fields at unnaturally high concentrations predisposing crop and crop products to residue accumulation (Kang et al 2015). In addition, the chemical class has been reported as the most toxic substance and habitually associated with endocrine disruption (Aguilar-Garduño et al 2013), cancer (Catherine et al 2016) and hypospadias (Michalis et al 2014), nervous disorders (Lee et al 2021) following exposure. Indeed, diazinon is among the most detected organophosphate in crop products despite its ban in some countries (Sapbamrer and Hongsibsong 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The chemical may also be volatilized, absorbed by plants or undergo microbial breakdown (Harper et al 2009). The hazardous aspects of diazinon and diazoxon to human include; endocrine disruption (ElMazoudy and Attia 2012), nervous disorders (Lee et al 2021), and liver and kidney damage (Cakici and Akat 2013) and potential to impact on ecosystem balance.…”
Section: Introductionmentioning
confidence: 99%